Komposisi botani dan kapasitas tampung hijauan di pinggiran jalan raya kawasan wisata hutan pinus Cikole Lembang - Syifa Nurjannah; Sari Suryanah; Nilawati Widjaja; Zaki Zaidan (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2026)
The research was conducted from late July to early August 2024 on the roadsides of the Cikole pine forest tourist area, Lembang. The study aimed to analyze the botanical composition and carrying capacity of forage in the surrounding area. The sampling method used was purposive sampling through direct field observation at the target locations. Sampling was conducted along roadsides around the pine forest at 10 sampling points. The distance between points was 400 meters, and at each point, five samples were taken, resulting in a total of 50 samples. Sampling used randomly placed 50 x 50 cm quadrants. The forage obtained was then cut and weighed to determine the fresh weight of the samples. The results showed the presence of 28 forage species, dominated by several forages, including Ageratina riparia, Cyperus rotundus, Miconia crenata, Digitaria sanguinalis, and Oplismenus burmannii. The carrying capacity of forage on the roadsides of the Cikole pine forest tourist area is 1.06 UT/ha/year, with fresh forage weight production of 13.38 tons/ha/year, and dry forage weight production of 5.7 tons/ha/year.